2020
DOI: 10.1111/nrm.12288
|View full text |Cite
|
Sign up to set email alerts
|

Statistical modeling of monthly rainfall variability in Soummam watershed of Algeria, between 1967 and 2018

Abstract: The monthly precipitations obtained during 51 years of measurement in 24 stations of Soummam watershed in Algeria were analyzed to describe rainfall trends and aridity state of the area using statistical modeling. The choice of distribution laws was justified by comparing fitting results of different distributions laws used in literature reviews. Hence, the p values proved that Generalized Extreme Value, Weibull (3) and Logistic the distribution law are more adequate to analyze rainfall frequencies in differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Vegetation growth is well‐described by the remotely sensed Normalized Difference Vegetative Index (NDVI), which primarily depends on external climatic factors (Tucker et al, 1985; Ziaeevafaeyan et al, 2018). Precipitation is the dominant factor on the variations of vegetation growth in the arid and semi‐arid areas (Aieb et al, 2020; Song et al, 2018). Therefore, NDVI is highly sensitive to interannual variability of precipitation.…”
Section: Introductionmentioning
confidence: 99%
“…Vegetation growth is well‐described by the remotely sensed Normalized Difference Vegetative Index (NDVI), which primarily depends on external climatic factors (Tucker et al, 1985; Ziaeevafaeyan et al, 2018). Precipitation is the dominant factor on the variations of vegetation growth in the arid and semi‐arid areas (Aieb et al, 2020; Song et al, 2018). Therefore, NDVI is highly sensitive to interannual variability of precipitation.…”
Section: Introductionmentioning
confidence: 99%
“…The Soummam valley watershed is one of the 17 largest watersheds in Algeria (Aieb et al, 2020). It covers an area of 9125 km 2 and is characterized by an irregular shape delimited mainly by the foothills of the Hodna mountains to the south, the Bouira plateau to the west, the Babors mountain chain to the east, and the Djurdjura mountain range to the North.…”
Section: Study Areamentioning
confidence: 99%
“…[9] obtained the monthly precipitations during 51 years of measurement in 24 stations of Soummam watershed in Algeria and analysed them to describe rainfall trends and aridity state of the area using statistical modeling. According to [9], the results of the p values showed that the Generalized Extreme value, Weibul (3) and logistic distribution laws were more adequate to analyze rainfall frequencies in different parts of the watershed. The diagnostic given by Q-Q plot P-P plot and survival regression curve was used to show the period of wetness and dryness in the northeastern and southwestern part of the watershed respectively.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The diagnostic given by Q-Q plot P-P plot and survival regression curve was used to show the period of wetness and dryness in the northeastern and southwestern part of the watershed respectively. In [9], study given by the De Martonn index was then used to explain the consequences of climate change by a new form of aridity in the watershed between 1994 and 2018.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation